Analisis Faktor Pengaruh Keputusan Pembelian pada Bisnis Digital E-Commerce Shopee - Feblicia, Shirley; Cuandra, Fendy (https://jurnal.binamandiri.ac.id/, 2022)
In 2021 it was found that Shopee was the number one e-commerce application with the most visitors, while the level of visitors from other e-commerce applications was under Shopee. Seeing the high level of visitors and consumer satisfaction as well as the number of purchasing decision makers on the Shopee application is the reason behind the author to carry out research on the factors that influence purchasing decisions in business digital Shopee’s e-commerce. The problem approach uses statistical methods starting with the procedures for collecting data, categorizing, summarizing, and delivering data on a phenomenon, and with SmartPLS 3 for descriptive statistical testing, testing the outer or inner model data quality along with the model fit test. The results showed that brand image, price, and product knowledge have a significant positive effect on Shopee’s purchasing decisions. Meanwhile, the promotion has no influence on purchasing decisions.